Panegyrics, Poetry and Hair in the Late First and Early Second Century AD. Issue 1 (1st January 2021) - Sande, Siri
Abstract : This article confronts descriptions (1) in the Younger Pliny's panegyric to Trajan of the outward appearance of the empress Plotina with portraits showing the coiffures of Plotina and other women in high society, (2) in Statius' Silvae of the artfully arranged hair of young slaves with monuments showing such delicati . It is argued that these descriptions serve to emphasise the ability of those praised (the emperor and the recipients of Statius' poems) to shape and control the nature of others (Plotina and the delicati ).